The CCAFS Regional Agricultural Forecasting Tool (CRAFT) will help bring powerful advance information tools to farmers and agricultural decision makers, better allowing them to manage within-season climate risk to agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The software has been developed and is online for downloading.